Clostridium difficile toxin B induces morphological changes consistent with autophagy in the human adenocarcinoma cell line (HT-29): Toksin B bakterije Clostridium difficile povzroča morfološke spremembe, ki nakazujejo proces avtofagije v človeških črevesnih epitelnih celicah HT-29 - Zemljič, Mateja; Lipovšek, Saška (Acta Medico-Biotechnica, 2021)
Purpose: Toxin B (TcdB) is a product of the bacteria Clostridium difficile, and can trigger apoptosis or necrosis. In the present manuscript, we proposed that TcdBVPI and TcdB8864 would cause morphological changes in cultured cells that are characteristic of autophagy, a constitutive cellular event closely linked with apoptosis or necrosis.Methods: We examined an in vitro model of cultured HT-29 cells to determine the occurrence of autophagy. The cells were incubated separately with TcdBVPI and TcdB8864 for 2 to 24 hours, and then examined using transmission electron microscopy.Results: In HT-29 cells, ultrastructural changes were observed following 8 hours of treatment with TcdBVPI and TcdB8864. Upon exposure to both toxins, complex changes occurred that affected the cellular framework, including the dilated regions of the granular endoplasmic reticulum, the Golgi apparatus, as well as electron-lucent and electron-dense autophagosome-like structures. Additionally, lipid droplets were present in the cytoplasm of HT-29 cells.Conclusion: Our findings indicate that TcdBVPI and TcdB8864 indeed induce ultrastructural changes in HT-29 cells. The presence of these autophagic structures in the cytoplasm of the HT-29 cells suggests that autophagy may be induced during treatment by both toxins. Therefore, this effect could represent an important protective mechanism for cell survival.
Keywords: autophagy; HT–29, toxin; ultrastructure